Influence of simultaneous intercropping of maize-bean with input of inorganic or organic fertilizer on growth, development, and dry matter partitioning to yield components of two lines of common bean - Suárez, Juan Carlos; Anzola, José Alexander; Contreras, Amara Tatiana; Salas, Dina Luz; Vanegas, José Iván; Urban, Milan Oldřich; Beebe, Stephen E.; Rao, Idupulapati M. (MDPI, 2022)
Intercropping is a common practice among smallholder farmers cultivating common bean (Phaseolus vulgaris L.) and maize (Zea mays L.). It affects agronomic performance, dry matter partition- ing, and grain yield. Simultaneous intercropping of common bean with maize can influence growth, development, and dry matter partitioning of grain of common bean. The main objectives of this study are to: (i) evaluate the dynamics of growth and development of the different vegetative organs, and (ii) determine the efficiency in dry matter partitioning to yield components of two common bean lines grown under monoculture compared with two simultaneous intercropping patterns (pattern 1, pattern 2) with maize and managed with two types of fertilizer application. A randomized complete block design (RCBD) with 3 replications was used in a nested trifactorial arrangement in split-plot scheme. The field experiment was conducted in two seasons under conditions of acid soils and high temperatures in the western Amazon region of Colombia. Simultaneous intercropping patterns 1 and 2 had a negative effect on growth dynamics of maize compared to maize monoculture. But the two bean lines when associated with maize showed no significant differences on growth dynamics under both types of fertilizer application. Under both intercropping patterns, the maize cobs were larger, a condition that increased the number of grains, but with smaller size of grains compared to monoculture. In the case of two bean lines, the growth and development responses were different: under monoculture the number of pods and seeds per plant was higher while the number of grains per pod increased under intercropping patterns. Among the two bean lines, 100-seed weight was significantly higher in BFS 10 compared to ALB 121. At the grain yield level of common bean, the simultaneous intercropping pattern increased 516 kg ha−1 and 993 kg ha−1 more than that obtained in monoculture (4936 kg ha−1) with inorganic and organic fertilizer, respectively. Results from this study indicated that smallholders in the Amazon region of Colombia can achieve higher grain yield through the implementation of simultaneous intercropping of maize with common bean line (BFS 10) under organic fertilizer application.